Pengaruh Laju Alir Udara terhadap Konstanta Pengeringan Bunga Telang (Clitoria ternatea) Menggunakan Tray Dryer - Laily Isna Ramadhani; Irwan Hidayatulloh; Dhyna Analyes Trirahayu (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The drying process in this study was carried out using a tray dryer at a drying air temperature of 60oC and a relative humidity of 17.8% by varying the flow rate, namely 1.6, 2.4 and 3.2 m/s. An analysis of the decrease in water content and drying rate constant was carried out to determine the effect of variations in flow rate on these two parameters based on experimental data and corroborated by correlation analysis and statistical significance. Variations in the flow rate of the drying air have an impact on reducing the water content of the butterfly pea flower by 57-60%, where based on the significance test, the results show that the relationship between the two variables is not statistically significant. In addition to the reduction in water content, the drying rate constant was also investigated in this study, where the largest drying rate constant was 0.0154 kgH2O/m2.minute when a drying air flow rate of 3.2 m/s was used.